EFFECT OF SIZE OF COMPANY AND LEVERAGE OPERATIONS AGAINST income smoothing MANUFACTURING COMPANY STOCK EXCHANGE IN JAKARTA - Nugroho, Bintoro Wahyu; Nursasmita, Ak., Drs. H. Irfan (Accounting, 2009)
The purpose of this study was to determine whether there is influence of firm size and operating leverage of income smoothing manufacturing companies in Jakarta Stock Exchange. The problem in this research is